Le pouvoir féminin dans L’École des Femmes et dans Le Jeu de l’amour et du hasard - Porubek, Lilla (Kansas State University, 2016)
In this comparative analysis of Molière’s, L’École des Femmes and Marivaux’s, Le Jeu de l’amour et du hasard, I examine the potential for agency on the part of the female protagonists Agnès and Silvia. Despite the limitations placed upon women in the patriarchal society of seventeenth and eighteenth century France, each character overcomes various obstacles in order to assert freedom of choice and expression in matters of the heart. The first chapter of this study, “L’amour et le mariage” focuses on love and marriage and the representation of these two concepts in terms of feminine power. These plays offer the opportunity to observe different types of perceptions regarding love and marriage and suggest that marriage based on mutual love is advantageous for women and tends to reinforce her power, as love is a strong motivation for appropriate partner choice. The second chapter, “La relation entre l’homme et la femme” analyses the relationship between the feminine and masculine figures of each play. Both authors give multiple cases of male-female interaction and suggest that men’s behavior is an important part of feminine power as women can make the decision about the appropriateness of the partner based on their observed behavior. While Molière gives the example of the negative and ignorant father-lover figure, Marivaux presents the ideal father image who encourages his daughter to make decisions based on her own best interests. The third chapter, “Le Masque: Le déguisement et le pouvoir féminins” examines the way in which the female protagonist is capable of improving her own situation. In each work, one can observe the woman’s creative behavior as a means by which she accomplishes her goal, to be able to choose a partner based on mutual love independently, supported by a benevolent father.
Keywords: Molière; Marivaux; L’École des Femmes; Le Jeu de l’amour et du hasard; Pouvoir; Mariage; Déguisement